(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed to study the impact of financing international humanitarian organizations in the Syrian Arab Republic on some economic indicators represented by gross domestic product, unemployment, and exchange rate during the period 2000-2020. The researcher relied on the descriptive analytical approach to describe the reality of financing in international organizations in Syria and analyzed the financing impact of these organizations on various economic indicators, in addition to the economic measurement method to show the impact of the relationship between the variables studied, using the Spss24 program. The researcher achieved to many results, the most important of which was that there is a significant relationship between funding humanitarian organizations in The Syrian Arab Republic and the economic indicators under study.